THE IMPACT OF HUMAN RESOURCE COMPETENCY, IMPLEMENTATION OF GOVERNMENT ACCOUNTING STANDARDS, IMPLEMENTATION OF LOCAL FINANCIAL ACCOUNTING SYSTEM, AND NEW PUBLIC MANAGEMENT ON THE QUALITY OF THE FINANCIAL REPORTS OF THE BANDAR LAMPUNG CITY GOVERNMENT - Hartati, Siti; Dewi, Fajar Gustiawaty (GoAcademica Research dan Publishing, 2024)
The policy change from centralization to decentralization strengthens regional autonomy in financial management, regulated to be transparent and accountable in accordance with Law no. 17 of 2003. Regional financial reports, which are audited by the BPK and submitted to the DPRD, are essential for policy making and evaluating the effectiveness of the use of funds. However, the quality of reports is often inadequate, a reflection of competency gaps in financial management. The objective of this study is to examine the impact of human resource competency, the application of government accounting standards, the adoption of local financial accounting systems, and New Public Management on the quality of financial reporting by the Bandar Lampung municipal government. The study employs a quantitative methodology, utilizing comparative causal analysis techniques. Findings from the study reveal that human resource skills, the application of governmental accounting norms, and local financial accounting systems positively influence the quality of the financial statements of the Bandar Lampung City Government, suggesting that effective implementation enhances report quality. However, New Public Management did not show significant influence, which may be caused by a lack of understanding of this concept in Bandar Lampung City.